Euthanasia: right derived from the dignity of the person? - Muñoz Góngora, Yoseline (2021)
The constitutional protection process initiated by the office of the ombudsman in favor of Ana Estrada, has placed euthanasia at the center of the political and social debate in our country. Euthanasia, far from being a practice in favor of the person and in accordance with the defense of their dignity, proposes a simple way out of situations of pain. Because behind the screen of the self-determination and the complete development of freedom, a state is recognized that presents itself as a source of salvation from suffering, that is not only the product of a terminal illness, but of any situation that implies build a voluntary and free act of ending your own life. The importance of family and professional support in the face of physical and emotional pain is lost from sight, as well as the need for the state to develop a series of public policies that allow the implementation of palliative care in our country.